2002
DOI: 10.1016/s1470-0328(02)01686-5
|View full text |Cite
|
Sign up to set email alerts
|

The Klippel–Trenaunay syndrome in pregnancy

Abstract: Case reportA 21 year old primipara was referred to our unit for advice regarding mode of delivery. The woman was 38 weeks pregnant and had an oblique lie. Her pregnancy had been uncomplicated. However, she had a large congenital haemangioma of the left buttock and thigh ( Fig. 1) extending to the lower leg and foot. There was a macular telangiectatic haemangioma that was associated with lateral venous varicosities that had developed over the past few years and had become worse in pregnancy. Both lower limbs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
5
1
1
Order By: Relevance
“…The high prevalence of VTE and PPH is in accordance with previously published case reports and case series (Table S1). 7,16,17 Severe complications such as paraplegia and uterine prolapse were reported in case studies, 8,9 but were not found in our study. In addition, our data are in contradiction with current literature on pregnancy outcomes in patients with KTS.…”
Section: Discussioncontrasting
confidence: 63%
“…The high prevalence of VTE and PPH is in accordance with previously published case reports and case series (Table S1). 7,16,17 Severe complications such as paraplegia and uterine prolapse were reported in case studies, 8,9 but were not found in our study. In addition, our data are in contradiction with current literature on pregnancy outcomes in patients with KTS.…”
Section: Discussioncontrasting
confidence: 63%
“…Most reported cases have resulted in delivery due to hemorrhage during the second or third trimester [3][4][5][6][7][8][9][10][11]. Cervical varicosities diagnosed during pregnancy have been associated with maternal in utero exposure to diethylstilbestrol, Klippel-Trenaunay syndrome, and abnormal placentation [3,[7][8][9][10][11][12][13][14]. Although most cases occur in the setting of placenta previa, there have been cases reported without concurrent abnormal placentation [3].…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is no indication for caesarean section other than known obstetric indications in cases of the Klippel-Trenaunay syndrome, which is a congenital vascular disorder that often presents vulvar varicosities (4)(5)(6)(7)(8) . However, some reports (2,3,(4)(5)(6) , but not all (7)(8)(9)(10) , have shown that caesarean delivery should be considered in cases of large vulvar varicosities. There is no evidence that either mode of delivery is advantageous in cases of huge vulvar varicosities, and no data are available to quantify the risk of rupture during a vaginal delivery.…”
Section: Discussionmentioning
confidence: 99%